Prevalência de Dismenorreia e sintomas menstruais em mulheres brasileiras: estudo transversal - Oliveira, Raissa Fernanda de (Universidade Federal de São Carlos, 2021)
Introduction: Dysmenorrhea is defined as cyclic pelvic pain related to the menstrual period and can be classified into primary (PD) or secondary dysmenorrhea, due to increased synthesis and release of prostaglandins. Symptoms associated with PD can impact women's quality of life . Method: This is a cross-sectional study developed at the Research Laboratory for Physiotherapy in Women's Health (LAMU), Department of Physiotherapy, Federal University of São Carlos (UFSCar) and approved by the Ethics and Research Committee on Human Beings. The research was disseminated online through social media and data collection was performed through Google's online forms platform, in which a semi-structured questionnaire was inserted regarding dysmenorrhea and associated factors and the Numerical Scale of Pain to assess dysmenorrhea in the last 5 years, the last 3 cycles and the last menstrual cycle. The association between qualitative variables was performed using Pearson's Chi-Square Test. The quantification of this association was measured using multinomial logistic regression models, with calculation of Odds Ratio and confidence interval. A significance level of 5% was considered. Result: 10070 women residing in Brazil answered the questionnaire, with an average age of 25.2 years (± 6.4). The prevalence of PD was 61.6%, considering the last menstrual cycle 78.1% (dysmenorrhea in the last 5 years), with 21.2% (last cycle) to 28.4% (last 5 years) of women reported the presence of menstrual cramps in severe form. The most common associated symptoms were indisposition, abdominal bloating and irritability. Women aged 18 to 23 years had a 1.4-fold increased risk of having moderate dysmenorrhea. In addition, nulliparous women are at a 1.4-fold increased risk for moderate pain and 1.4-fold for severe dysmenorrhea. The presence of menstrual pain since adolescence increases the risk of moderate pain by 4.3 times and 7.2 for severe pain in adulthood. Conclusion: The prevalence of dysmenorrhea found in this study ranged from 61.6% to 78.1% when considering the three time periods of the questionnaire (last cycle, last 3 cycles and last 5 years). In addition to dysmenorrhea, women had several associated symptoms, the most common of which were indisposition, irritability and a feeling of abdominal bloating. Moderate dysmenorrhea is associated with younger women (18 to 23 years old), nulliparity and the occurrence of menstrual pain since adolescence.
Prevalence of dysmenorrhea and menstrual symptoms in Brazilian women: a cross-sectional study
Keywords: Menstruação dolorosa; Dor pélvica; Prevalência; Classificação; Distúrbios menstruais; Sintomas menstruais; Dor menstrual; Menstrual pain; Menstrual symptoms; Menstruation disturbances; Classification; Prevalence; Pelvic pain; Dysmenorrhea; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL